1998
DOI: 10.1002/(sici)1099-0844(199809)16:3<173::aid-cbf783>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial sensitivity to AZT

Abstract: The possibility of tissue-specific effects regarding mitochondrial sensitivity to AZT was evaluated in this study. When mitochondria isolated from liver, kidney, skeletal and cardiac muscle were oxidizing glutamate, a dose-dependent inhibition by AZT of state 3 respiration was observed; using succinate as substrate the inhibition occurred only in skeletal and cardiac muscle mitochondria. The same results were obtained with FCCP-uncoupled mitochondria. NADH oxidase of intact and disrupted mitochondria, isolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Several studies have shown a direct effect on complex I by NRTIs, for example we have demonstrated an apparent decoupling of complex I with AZT in vitro , and others have suggested an alteration of electron flow through complex I (Pereira et al, 1998;Valenti et al, 2002) as well as alterations in NADH linked respiration with AZT and ddC (Modica-Napolitano, 1993;Skuta et al, 1999;Szabados et al, 1999). Although complex I does have a nucleotide binding site (NADH), there is no evidence to suggest AZT or other NRTIs interfere with NADH binding.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…Several studies have shown a direct effect on complex I by NRTIs, for example we have demonstrated an apparent decoupling of complex I with AZT in vitro , and others have suggested an alteration of electron flow through complex I (Pereira et al, 1998;Valenti et al, 2002) as well as alterations in NADH linked respiration with AZT and ddC (Modica-Napolitano, 1993;Skuta et al, 1999;Szabados et al, 1999). Although complex I does have a nucleotide binding site (NADH), there is no evidence to suggest AZT or other NRTIs interfere with NADH binding.…”
Section: Introductionmentioning
confidence: 61%
“…Mitochondrially localized protein kinases such as PKAwhich regulate complex I activity -may provide a mechanistic link between NRTI related disruptions in complex I activity/respiration and evidence of endogenous kinase inhibition by NRTIs. NRTIs (AZT in particular) have been shown to inhibit various nucleotide kinases (Munch-Petersen et al, 1991;McKee et al, 2004;Rylova et al, 2005) as well as metabolic and regulatory kinases (Barile et al, 1994;Pereira et al, 1998;Carnicelli et al, 2006). However, to date, no studies involving PKA and NRTIs have been published.…”
Section: Introductionmentioning
confidence: 99%
“…Carbonyl groups also may be introduced into proteins by glycoxidation and lipid peroxidation products. 20,21 The absence of such a response in CSF obtained from patients with MS suggests that neuroinflammatory responses alone are likely not sufficient to cause mitochondrial dysfunction. 14 Once the proteins are oxidized they are cleaved by proteases 14 and thus would likely have access to the CSF.…”
Section: Discussionmentioning
confidence: 99%
“…Indicating a severe effect at the level of respiratory complex-I [14], particularly at the sub-complex-I β [15]. The enhanced H 2 O 2 content induces a large increase in reactive oxygen species (ROS) and peroxynitrite production that causes single strand DNA breaks, lipid peroxidation, protein oxidation/nitration, and mitochondrial DNA (mtDNA) oxidation [16, 17].…”
Section: Introductionmentioning
confidence: 99%